A STUDY ON THE LEVEL OF THE KNOWLEDGE OF ADVANCED LEVEL STUDENTS RELATED TO DOMESTIC APPLICATION IN CHEMISTRY. - Bandula Kumara K.D. (International Engineering Journal For Research & Development, 2023)
Chemistry is an important part of life. Human beings are also chemical in nature. To understand how we work as well as the universe that we are part of chemistry is needed. Chemistry helps us to understand the world around us. It is in food we eat, cloths we wear, water we drink, medicine we take etc. Therefore chemistry is considered as one of the major subjects in science streams at secondary senior students (grade 12 and 13) in Sri Lanka. In Sri Lankan Advance level curriculum (secondary senior level) chemistry is a compulsory subject for students in physical and bioscience stream. Although the facts, patterns and principals of chemistry were broadly discussed in the syllabus it is observed that the knowledge of the chemicals used in day to day life is not sufficient. This research was done with the intention of identifying the level of knowledge of A/L students in household chemistry, perusing subject content related to household chemistry in other countries and recommending subject content that should be included in A/L syllabus related to household chemistry . To achieve the objectives following methodology was used. First a diagnosis test was administered to identify the knowledge of students regarding the household chemistry. Another questionnaire was used to check the ideas of teachers regarding the level of students as well as the subject content that should be included to the syllabus. Relevant topics were identified referring to the syllabus of other countries. Including facts regarding household chemistry was accepted in the discussion with University lectures and Lectures of NIE (National Institute of Education). The results of diagnosis test proved deficiency in knowledge of A/L students regarding household chemistry. It is strongly proved when analyzing the questionnaire given to teachers. According to the research following subject matters were identified to be included in the A/L syllabus. Chemical in food, chemistry of some important pharmaceutical, chemistry of cleaning agent, chemistry of paints, chemistry of cosmetic can be recommended to include in A/L syllabus. Chemistry can be made an interesting subject for student by realizing them regarding application of chemistry in the real life situations.